Coriocarcinoma gástrico primario: reporte de caso - Palacios Soto, Pierre (2018)
Primary gastric choriocarcinoma (PGC) is an extremely rare and highly invasive tumor with rapid hematogenous spread. We present the case of a 57-year-old female patient who started with hematemesis and progressive episodes of melena, weight loss and epigastralgia. It is derived from the National Institute of Neoplastic Diseases where gastroscopy and biopsy are performed. Histological analysis reported pattern suggestive of PGC; that was confirmed by immunohistochemical analysis for human chorionic gonadotrophin and fetal alpha protein. Subsequently, the patient underwent a radical D2 gastrectomy with splenic preservation and tail of the pancreas preservation. Unfortunately, her evolution was not favorable and died due to the progression of the disease.